The Effect of Using Problem Based Learning Student Worksheet Model to Build Mathematical Problem Solving Ability for Class VIII Junior High School Students - Nurfadilla, Nurfadilla; Yuanita, Putri; Zulkarnain, Zulkarnain (FKIP-Universitas Riau, 2021)
This study aims to determine the effect of using student worksheet (LKPD) based on the Problem Based Learning model on the mathematical problem solving abilities of students of class VIII SMP Negeri 2 Pangean. This type of research was a quasi-experimental study with a pretest – posttest control group design. The population was all students of SMP Negeri 2 Pangean Indonesia in the 2019/2020 school year. Sampling method was using random sampling technique. Based on the results of data analysis, the posttest mean score in the experimental class was 85.45 and the average value in the control class was 54.5, meaning that the average value of the experimental class was higher than the control class. The two-mean difference test using the t test was significant (2-tailed) 0.000 <α = 0.05, which means that the posttest score of students 'mathematical problem solving abilities was different from the average posttest score of students' mathematical problem solving abilities. which uses scientific learning. So it can be concluded that there is an effect of the Problem Based Learning model on students' mathematical problem solving abilities.